CV. PRIMANTO PANGAN SELARAS - Muhammad Zainul Hakim; Raga Etsenna Wattimena; Husnul Khotimatussaudah (AIBPM Publisher, 2018)
The Primanto Pangan Selaras company is a food producer which produce fruit chips and “jenang”, located in the Batu City, precisely on Sumber Urip street number. 239, Tlekung, the owner of this company is Mr. Efri Gunawan. We choose Australia as a destination country, because the number of fruit chips like snake fruit & jackfruit are located the most in Asia, especially in Southeast Asia, and it’s quite rare in Australia, but from company data that has been obtained, it is known that the company is still focused on developing business in the home city because the company is relatively new. For the marketing strategy, our group advises the company to be more focus on promoting it products on social media, because nowadays, there are many social media users, and the other benefit is that marketing can be done abroad, we also plan to establish cooperation with Garuda in the export process. For human resources in this company, the company employs 4 employees, the reason the company employs 4 people is because the company's production machinery is quite efficient, and the marketing costs are carried out by the owner of the company itself, so there’s no marketing fee. Keywords: local business, fruit chips, export.